2018
DOI: 10.1021/acs.langmuir.7b04266
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Induced Structural Evolution of Silicon- and Oxygen-Containing Hydrogenated Amorphous Carbon: A Combined Spectroscopic and Molecular Dynamics Simulation Investigation

Abstract: Silicon- and oxygen-containing hydrogenated amorphous carbon (a-C:H:Si:O) coatings are amorphous thin-film materials composed of hydrogenated amorphous carbon (a-C:H), doped with silicon and oxygen. Compared to a-C:H, a-C:H:Si:O exhibits much lower susceptibility to oxidative degradation and higher thermal stability, making a-C:H:Si:O attractive for many applications. However, the physical mechanisms for this improved behavior are not understood. Here, the thermally induced structural evolution of a-C:H:Si:O w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…This influences the resulting thermo‐oxidative stability of the material: while for PIIID films, the sp 3 fraction only changed from 78 ± 3% to 61 ± 3%; for PECVD a‐C:H:Si:O films, the sp 3 fraction drops substantially to 36 ± 3% upon vacuum annealing. It should be noted that the PECVD a‐C:H:Si:O already possesses a greater degree of pure thermal stability under vacuum annealing than an undoped a‐C:H by the metric of activation energy for sp 3 →sp 2 C rehybridization …”
mentioning
confidence: 98%
See 4 more Smart Citations
“…This influences the resulting thermo‐oxidative stability of the material: while for PIIID films, the sp 3 fraction only changed from 78 ± 3% to 61 ± 3%; for PECVD a‐C:H:Si:O films, the sp 3 fraction drops substantially to 36 ± 3% upon vacuum annealing. It should be noted that the PECVD a‐C:H:Si:O already possesses a greater degree of pure thermal stability under vacuum annealing than an undoped a‐C:H by the metric of activation energy for sp 3 →sp 2 C rehybridization …”
mentioning
confidence: 98%
“…Metal‐doping (Cr, Pt, Au) leads to a unique optical absorbance spectrum, which makes such materials attractive in solar energy applications, for example . a‐C:H:Si:O has been shown to exhibit higher thermal and oxidative stability . The authors of this work recently demonstrated that the a‐C:H:Si:O films grown by PECVD with silicon and oxygen levels of, respectively, 6 ± 1 at.% and 3 ± 1 at.% exhibit a slightly‐enhanced thermal stability under high vacuum (HV) conditions compared to a‐C:H (with similar fraction of sp 2 ‐bonded carbon and hydrogen content).…”
mentioning
confidence: 99%
See 3 more Smart Citations